Skewness in bee and flower phenological distributions. Issue 1 (30th November 2022) - Stemkovski, Michael; Dickson, Rachel G.; Griffin, Sean R.; Inouye, Brian D.; Inouye, David W.; Pardee, Gabriella L.; Underwood, Nora; Irwin, Rebecca E.
Abstract: Phenological distributions are characterized by their central tendency, breadth, and shape, and all three determine the extent to which interacting species overlap in time. Pollination mutualisms rely on temporal co‐occurrence of pollinators and their floral resources, and although much work has been done to characterize the shapes of flower phenological distributions, similar studies that include pollinators are lacking. Here, we provide the first broad assessment of skewness, a component of distribution shape, for a bee community. We compare skewness in bees to that in flowers, relate bee and flower skewness to other properties of their phenology, and quantify the potential consequences of differences in skewness between bees and flowers. Both bee and flower phenologies tend to be right‐skewed, with a more exaggerated asymmetry in bees. Early‐season species tend to be the most skewed, and this relationship is also stronger in bees than in flowers. Based on a simulation experiment, differences in bee and flower skewness could account for up to 14% of pairwise overlap differences. Given the potential for interaction loss, we argue that difference in skewness of interacting species is an underappreciated property of phenological change.